Stereotypical hand movements in 144 subjects with Rett syndrome from the population-based Australian database - Carter, Philippa; Downs, Jenny; Bebbington, Ami; Williams, Simon; Jacoby, Peter; Kaufmann, Walter E.; Leonard, Helen (Movement disorders, 2010)
Stereotypic hand movements are a feature of Rett Syndrome but few studies have observed their nature systematically. Video data in familiar settings were obtained on subjects (n = 144) identified from an Australian population‐based database. Hand stereotypies were demonstrated by most subjects (94.4%), 15 categories were observed and midline wringing was seen in approximately 60% of subjects. There was a median of two stereotypies per subject but this number decreased with age. Clapping and mouthing of hands were more prevalent in girls younger than 8 years and wringing was more prevalent in women 19 years or older. Clapping was commoner in those with p.R306C and early truncating mutations, and much rarer in those with p.R106W, p.R270X, p.R168X, and p.R255X. Stereotypies tended to be less frequent in those with more severe mutations. Otherwise, there were no clear relationships between our categories of stereotypies and mutation. Approximately a quarter each had predominantly right and left handed stereotypies and for the remaining half, no clear laterality was seen. Results were similar for all cases and when restricted to those with a pathogenic mutation. Hand stereotypies changed with increasing age but limited relationships with MECP2 mutations were identified. © 2009 Movement Disorder Society